Chinese striped-neck turtles vocalize underwater and show differences in peak frequency among different age and sex groups - Zhou, Lu; Lei, Jinhong; Zhai, Xiaofei; Shi, Haitao; Wang, Jichao (PeerJ, 2023)
Background Turtle vocalizations play an important role throughout their lives by expressing individual information (position, emotion, or physiological status), reflecting mating preferences, and synchronizing incubation. The Chinese striped-neck turtle (Mauremys sinensis) is one of the most widely distributed freshwater turtles in China, whose wild population is critically endangered. However, its vocalization has not been studied, which can be the basis for behavioral and ecological studies. Methods Five different sex–age groups of turtles were recorded underwater in a soundproof room. Cluster analysis and principal component analysis for classification of Chinese striped-neck turtle calls were unreasonable. The turtle calls were manually sought using visual and aural inspection of the recordings in Raven Pro 1.5 software and classified according to differences perceived through auditory inspection and the morphological characteristics of the spectrograms. The results of similarity analysis verified the reliability of manual classification. We compared the peak frequency of the calls among different age and sex groups. Results We identified ten M. sinensis call types, displayed their spectra and waveforms, and described their auditory characteristics. Most calls produced by the turtles were low-frequency. Some high-frequency call types, that are common in other turtle species were also produced. Similar to other turtles, the Chinese striped-neck turtle generates harmonic vocalizations. Courtship behaviors were observed when one of the call types occurred in the mixed-sex group. Adult females produced more high-frequency call types, and subadult males had higher vocalizations than other groups. These results provide a basis for future research on the function of vocalizations, field monitoring, and conservation of this species.
Keywords: Sound recording; Underwater vocalization; Call types; Peak frequency; Chinese striped-neck turtles; Mauremys sinensis; Sex difference